1971
DOI: 10.1139/v71-589
|View full text |Cite
|
Sign up to set email alerts
|

The Photolysis and Radiolysis of Simple Mercaptans in Dilute Glassy Matrices

Abstract: The e.p.r. spectrum of thiyl radicals is obtained when dilute solutions of aliphatic mercaptans are photolyzed in a xenon matrix at 77 OK. No proton hyperfine structure is observed at low concentrations of thiol but it appears at higher concentrations due to the reaction of hot hydrogen atoms with solute mercaptan molecules. When small amounts of the thiols are dissolved in glassy hydrocarbon matrices such as 3-methylpentane, there is produced after photolysis hyperfine structure characteristic of the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…20 Additional ESR experiments obtained with small model thiols also suggest the possibility for a formal 1,2-hydrogen transfer in thiyl radicals, that is, the observation of • CH 2 SH radicals after the photolysis of CH 3 SH, 22 and the detection of CH 3 C • H-SH radicals after photolysis of CH 3 CH 2 SH. 23 Theoretical calculations have examined activation energies for intramolecular hydrogen transfer reactions in GS • . 24 Here, the hydrogen transfer between the thiyl radical and the α C−H bond of γ-Glu displays a rather low activation energy of ΔG ⧧ = 37−42 kJ mol −1 , whereas the 1,3-hydrogen shift within the Cys residue shows ΔG ⧧ = 110 kJ mol radicals from Cys (CysS • ) exists, both in the gas phase 25 and in solution.…”
Section: ⇌ + +mentioning
confidence: 93%
See 2 more Smart Citations
“…20 Additional ESR experiments obtained with small model thiols also suggest the possibility for a formal 1,2-hydrogen transfer in thiyl radicals, that is, the observation of • CH 2 SH radicals after the photolysis of CH 3 SH, 22 and the detection of CH 3 C • H-SH radicals after photolysis of CH 3 CH 2 SH. 23 Theoretical calculations have examined activation energies for intramolecular hydrogen transfer reactions in GS • . 24 Here, the hydrogen transfer between the thiyl radical and the α C−H bond of γ-Glu displays a rather low activation energy of ΔG ⧧ = 37−42 kJ mol −1 , whereas the 1,3-hydrogen shift within the Cys residue shows ΔG ⧧ = 110 kJ mol radicals from Cys (CysS • ) exists, both in the gas phase 25 and in solution.…”
Section: ⇌ + +mentioning
confidence: 93%
“…the observation of • CH 2 SH radicals after the photolysis of CH 3 SH, 22 and the detection of CH 3 C • H-SH radicals after photolysis of CH 3 CH 2 SH. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photolysis of thiol species of the form R–SH results mainly in scission of C–S and S–H bonds with the main products being radicals and, depending on photolysis conditions, various radical recombination products. In 195 nm flash photolysis experiments on gaseous CH 3 SH, Callear et al observed formation of CH 3 S, CH 3 , and other radicals using UV absorption spectroscopy while 254 nm photolysis of C 2 H 5 SH in a xenon matrix was shown to produce the thiyl radical C 2 H 5 S* . Photolysis of CH 3 SH vapor at 254 and 214 nm has been shown to produce H 2 , H 2 S, C 2 H 4 , C 2 H 6 , and CH 3 SSCH 3 ; C 2 H 5 SH vapor photolyzed under the same conditions produced H 2 , H 2 S, C 2 H 4 , C 2 H 6 , and C 2 H 5 SSC 2 H 5 …”
Section: Introductionmentioning
confidence: 99%
“…In 195 nm flash photolysis experiments on gaseous CH 3 SH, Callear et al 52 observed formation of CH 3 S, CH 3 , and other radicals using UV absorption spectroscopy while 254 nm photolysis of C 2 H 5 SH in a xenon matrix was shown to produce the thiyl radical C 2 H 5 S*. 55 56 and C 2 H 5 SSC 2 H 5 . 57 Hydrogen atom production and escape of H 2 from the matrix cage has been reported as well, producing even more complex, dehydrogenated species, where photolysis of methanethiol at 121 nm in a nitrogen matrix at 14 K leads to formation of CH 4 , CS, CS 2 , CH 3 , and H 2 CS as the main products.…”
Section: Introductionmentioning
confidence: 99%